An Improved Multi-Cycle Deadlock Detection and Resolution Algorithm for Distributed Systems - Mohsen Askari; Rozita Jamili Oskouei (Universitas Sriwijaya, 2014)
Distributed systems exhibit a high degree of resource and data sharing creating a state in which deadlocks might make their appearance. Since deadlock detection and resolution is one of the important concerns in distributed systems which lead to minimizing available resources, therefore instigating the system throughput decrease. Our proposed algorithm detects and resolves the multi-cycle deadlocks, whether the initiator is involved in the deadlock cycle directly or indirectly. Also the chance of phantom deadlock detection is minimized. This algorithm not only can manage the simultaneous execution of it but also detects the multi-cycle deadlocks in the distributed systems. Our algorithm introduces a modified probe and victim message structure. Moreover, no extra storage required to store prob message in each node which is known as memory overhead in the distributed systems.